Application of Sen's Capability Approach to Outcome Measurement in Mental Health Research: Psychometric Validation of a Novel Multi-dimensional Instrument (OxCAP-MH). Issue 1 ( 2014) - Vergunst, Francis; Jenkinson, Crispin; Burns, Tom; Simon, Judit
No abstract available